Analyzing the Service Quality of Private Secondary Schools in Sri Lanka from Student’s Perspective with Special Reference to a Reputed Private Secondary School in Colombo - Jayawardena , N.S (Asian Journal of Empirical Research, 2018)
The proposed study analyses the service quality levels of private secondary school education in Sri Lanka from the perspective of students. The aim of the research is to study service quality levels offered in private secondary schools to improve the quality of education levels in Sri Lanka. For this purpose a main private secondary school was used as the case study. It helps to develop strategies to school management and the respective administrative authorities. Furthermore, the policy implications based on the final findings of this particular research will be used to enhance the required productivity levels and quality standards of Sri Lankan private secondary schools. This is a quantitative study and intends to use the sample size of 400 students out of the total body of over 2500 student population. The survey questionnaire derived from SERVQUAL model which consists of the five dimensions which are reliability, responsiveness, empathy, assurance and tangibles. Data been analyzed using the 7 point Likert scale and the SPSS statistical software to reach the ultimate findings based on the service quality dimensions.